Retrospective cost-effectiveness of the 23-valent pneumococcal polysaccharide vaccination program in Australia. Issue 42 (8th October 2018) - Chen, C.; Beutels, P.; Wood, J.; Menzies, R.; MacIntyre, C.R.; McIntyre, P.; Newall, A.T.
Abstract: Background: The Australian infant pneumococcal vaccination program was funded in 2005 using the 7-valent pneumococcal conjugate vaccine (PCV7) and the 13-valent conjugate vaccine (PCV13) in 2011. The PCV7 and PCV13 programs resulted in herd immunity effects across all age-groups, including older adults. Coincident with the introduction of the PCV7 program in 2005, 23-valent pneumococcal polysaccharide vaccine (PPV 23) was funded for all Australian adults aged over 65 years. Methods: A multi-cohort Markov model with a cycle length of one year was developed to retrospectively evaluate the cost-effectiveness of the PPV23 immunisation program from 2005 to 2015. The analysis was performed from the healthcare system perspective with costs and quality-adjusted life years discounted at 5% annually. The incremental cost-effectiveness ratio (ICER) for PPV23 doses provided from 2005 to 2015 was calculated separately for each year when compared to no vaccination. Parameter uncertainty was explored using deterministic and probabilistic sensitivity analysis. Results: It was estimated that PPV23 doses given out over the 11-year period from 2005 to 2015 prevented 771 hospitalisations and 99 deaths from invasive pneumococcal disease (IPD) . However, the estimated IPD cases and deaths prevented by PPV23 declined by more than 50% over this period (e.g. from 12.9 deaths for doses given out in 2005 to 6.1 in 2015), likely driven by herd effects from infant PCV programs. The estimated ICER over the period 2005 to 2015 was approximately A224, 000/QALY gained compared to no vaccination. When examined per year, the ICER for each individual year worsened from 140, 000/QALY in 2005 to 238, 000/QALY in 2011 to 286, 000/QALY in 2015. Conclusion: The cost-effectiveness of the PPV23 program in older Australians was estimated to have worsened over time. It is unlikely to have been cost-effective, unless PPV23 provided protection against non-invasive pneumococcal pneumonia and/or a low vaccine price was negotiated. A key policy priority should be to review of the future use of PPV23 in Australia, which is likely to be more cost-effective in certain high-risk groups.